The Pietà study: epidemiological investigation on successful brain aging in Caeté (MG), Brazil. Methods and baseline cohort characteristics - Paulo Caramelli; Maira Tonidandel Barbosa; Emília Sakurai; Etelvina Lucas dos Santos; Rogério Gomes Beato; João Carlos Barbosa Machado; Henrique Cerqueira Guimarães; Antonio Lucio Teixeira (Arquivos de Neuro-Psiquiatria)
OBJECTIVES: To present the methods and baseline characteristics of the Pietà study, a population-based survey investigating successful brain aging in the oldest-old. METHOD: The study was conducted in Caeté (MG), Brazil. In 2007, 1,251 individuals aged 75+ years were living in the city and were invited to participate. Participants responded to a general health questionnaire and were submitted to clinical, neurological, cognitive, psychiatric and functional evaluations. A subgroup was submitted to neuropsychological testing, blood tests and magnetic resonance of the skull. Individuals were classified as having cognitive impairment-no dementia, dementia, parkinsonism, psychiatric disorders or successful brain aging. RESULTS: We evaluated 639 individuals (51.1% of the target population; 64% women), aged 81.4±5.2 years and with 2.7±2.6 years of schooling. Almost 30% of the elderly were illiterates and 82.1% belonged to middle/middle-low socioeconomic levels. Almost 50% were widows, but only 14.3% were living alone. CONCLUSION: The Pietà cohort is representative of the oldest-old Brazilian population. We believe the results of the study may contribute to increase our knowledge about healthy and pathological brain aging in the oldest-old.